2012
DOI: 10.1258/ar.2012.110303
|View full text |Cite
|
Sign up to set email alerts
|

Management of isolated non-traumatic renal artery dissection: report of four cases

Abstract: Conservative therapy is safe and effective when the renal artery is patent and blood pressure is controlled: we propose it as the first line of treatment, reserving interventional management for refractory cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Isolated nontraumatic RAD with unknown underlying cause is a rare condition. 1,5 In the literature, spontaneous RAD is defined as a dissection of the renal artery without underlying vascular disease, renal artery intervention, or trauma and approximately 200 isolated RAD cases have been reported. Spontaneous RAD is more frequently observed in males between the fourth and sixth decades of life.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Isolated nontraumatic RAD with unknown underlying cause is a rare condition. 1,5 In the literature, spontaneous RAD is defined as a dissection of the renal artery without underlying vascular disease, renal artery intervention, or trauma and approximately 200 isolated RAD cases have been reported. Spontaneous RAD is more frequently observed in males between the fourth and sixth decades of life.…”
Section: Discussionmentioning
confidence: 99%
“…The dissection may go unnoticed or present with flank pain, hypertension, deteriorating renal function, hematuria, and increased lactate dehydrogenase in serum. 1,8 Because of this, spontaneous RAD may be confused with more frequently seen diseases such as ureterolithiasis and acute pyelonephritis, and therefore, the diagnosis may be delayed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other cases involved medical treatment such as antihypertensive medications, pain control, and anticoagulation or antiplatelet agents. One case series of four patients, three of whom had dissections treated with conservative medical management, found that at 1-month follow-up after treatment with enoxaparin and aspirin, all three patients treated with medical management had normal kidney function, normal blood pressure, and had revascularization of the majority of their kidneys [8]. Another two cases of spontaneous renal dissection, which had only caused ischemia to a fraction of the kidney or were not associated with ischemia, were both successfully treated with conservative medical management involving anticoagulation and antiplatelet agents with a good outcome [9, 10].…”
Section: Discussionmentioning
confidence: 99%